Analisis Makna Kanji dengan Bushu Hihen - Saputra, Khusnul Immaji Husein; Rahayu, Ely Triasih; Kurniawan, Eko (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2022)
The purpose of this research to describe the meaning of the kanji that has hihen character in the manga Barakamon volume 10th, 11th, and 12th. This research is a qualitative descriptive study with data collection techniques and uses note-taking techniques. The research data was in the form of kanji that has hihen character in the manga Barakamon, volume 10th, 11th, and 12th. The method used to analyze and find out the meaning of the kanji is the rikusho kanji formation theory of naritachi kanji. The results show that there are ten kanji in the manga Barakamon, volume 10th, 11th, and 12th that has hihen character. Then, it was found the kanji that has bushu hihen have a similar characteristic to the sun, both in the form of the nature of the sun, the function of the sun for humans, and the phenomena that occur because of the sun.